Menjadi Manusia Spiritual-Ekologis Di Tengah Krisis Lingkungan Sebuah Review - Frederikus Fios (Jurnal Sosial Humaniora, 2019)
Natural damage resulting from development activities committed humanbeings cannot be avoided. The deforestation is happening reduces theamount of forest area of Indonesia from Sabang to Merauke. The cause of thedamage to our human nature as a subject of the spiritual-ecological. Thematerialist economic paradigm of mastering the mindset of human. Theprimacy of the spiritual-ecological neglected in development activities. Thisresearch aims to find an alternative relevant human model to restore naturein the midst of a crisis of the global environment and the context ofIndonesia in particular. This paper is developed using the method especiallyethical reflection. Finding a spiritual ecological thought as ontological basichuman life in harmony with nature. Become a spiritual-ecological humanbeing capable of providing solutions to the environmental crisis thathappened an minimize the environmental crisis for the sake of ecologicalsustainability of creation.